In-vitro Dissolution Profile and Other Physical Parameters Determination of Cimetidine Formulations - Benjamin U. Ebeshi; Samuel J. Bunu; Ebisindor V. Awala; Deghinmotei Alfred-Ugbenbo; Adesegun J. Kashimawo; Seimokumo S. Angaye; Kodilichukwu Oliobi (Pharmaceutical Science: New Insights and Developments Vol. 5, 2025)
Peptic ulcers are a category of disorders that manifest as a rupture in the intestinal epithelium that becomes saturated in acid and pepsin. It is the most frequent digestive tract disorder, with a global prevalence of 80% in developing and 40% in industrialised countries. The study aimed to compare the effectiveness and bioavailability using the in vitro dissolution method and assess other physicochemical properties of different brands of cimetidine tablets. Cimetidine is a model biopharmaceutics classification system (BCS) class-III medicine that is N-(amino sulfonyl)-3-[2 - [(diamine methylene) amino]-4-thiazolyl] methyl] thio] propanimidamide. It is a strong Histamine-2 (H2) receptor antagonist used in the treatment of peptic ulcers. Five (5) different brands of cimetidine tablets, labelled A–E, were purchased and used for the analysis. Physicochemical tests such as weight uniformity, hardness, disintegration, friability, and dissolution test were conducted following standard British pharmacopoeia procedures. Samples A-E conformed to the weight uniformity standard with a mean % weight deviation of 0.37 – 1.39 %, while E had 11.52% based on the batch used. Samples B and A had the highest mean kgf (10.5 and 9.7), while sample E had the lowest kgf (4.4), hence liable to mechanical damage. All the samples used for the analysis had below 1.0% friability. All the samples passed the disintegration test, with sample A having the longest disintegration time (4.44 minutes) and sample C having the shortest disintegration time (0.21 minutes). At 25.99 minutes, Sample A had the fastest disintegration rate. The method used in the analysis is accurate, precise, and cost-effective. The analysis does not require pretreatment of the drug and can compete with other existing methods in the routine quality control analysis of cimetidine in pharmaceutical formulation.